Trend in domestic and family violence against women in the period 2019/2020 in Itabuna/Bahia with emphasis on the SARS-CoV-2 pandemic: prevalence and associated factors (Research, Society and Development, 2022)
Introduction: Domestic and Family Violence against Women is a serious intersectoral and public health problem. With the advent of the pandemic caused by the new coronavirus, the implementation of social isolation as a containment measure to control the transmissibility of the disease, represented for women in situations of domestic violence an additional obstacle to the maintenance of their health and life. Objective: to estimate the prevalence and factors associated with Domestic and Family Violence against Women in the period 2019 and 2020 during the pandemic of COVID-19 in the municipality of Itabuna, Bahia, Brazil. Method: This is an epidemiological, observational, cross-sectional type study conducted in the municipality of Itabuna, Bahia, located in Northeastern Brazil, that allowed to estimate the prevalence and factors associated with the occurrence of MDV in the period of 2019 and 2020. To determine the differences between the frequencies of the characteristics in the years 2019 and 2020, the Chi-square test was used, and the significance level was considered 5% and the prevalence ratio as a measure of association. Results: The sample was composed of 2,304 occurrences of Domestic and Family Violence against Women, with a prevalence of the age group 35-64 years (43.4%), brown ethnicity (90.4%), heterosexual sexual orientation (99.3%); greater occurrence of psychological violence (37.1%), motivation by intrafamily violence (74.7%), with Module 4 presenting the highest number of occurrences (34.1%). Conclusion: There was a 15% increase in the total occurrences of Domestic and Family Violence against Women in the second semester of the year in which the SARS-CoV-2 pandemic occurred.